C7 vertebra homeotic transformation in domestic dogs – are Pug dogs breaking mammalian evolutionary constraints?. Issue 2 (14th May 2018) - Brocal, J.; De Decker, S.; José‐López, R.; Manzanilla, E. G.; Penderis, J.; Stalin, C.; Bertram, S.; Schoenebeck, J. J.; Rusbridge, C.; Fitzpatrick, N.; Gutierrez‐Quintana, R.
Abstract: The number of cervical vertebrae in mammals is almost constant at seven, regardless of their neck length, implying that there is selection against variation in this number. Homebox ( Hox ) genes are involved in this evolutionary mammalian conservation, and homeotic transformation of cervical into thoracic vertebrae (cervical ribs) is a common phenotypic abnormality when Hox gene expression is altered. This relatively benign phenotypic change can be associated with fatal traits in humans. Mutations in genes upstream of Hox, inbreeding and stressors during organogenesis can also cause cervical ribs. The aim of this study was to describe the prevalence of cervical ribs in a large group of domestic dogs of different breeds, and explore a possible relation with other congenital vertebral malformations (CVMs) in the breed with the highest prevalence of cervical ribs. By phenotyping we hoped to give clues as to the underlying genetic causes. Twenty computed tomography studies from at least two breeds belonging to each of the nine groups recognized by the Federation Cynologique Internationale, including all the brachycephalic 'screw‐tailed' breeds that are known to be overrepresented for CVMs, were reviewed. The Pug dog was more affected by cervical ribs than any other breed (46%; P  < 0.001), and was selected for further analysis. No association was found between the presence of cervical ribs and vertebral body formation defect, bifid spinous process, caudal articular process hypoplasia/aplasia and an abnormal sacrum, which may infer they have a different aetiopathogenesis. However, Pug dogs with cervical ribs were more likely to have a transitional thoraco‐lumbar vertebra ( P  = 0.041) and a pre‐sacral vertebral count of 26 ( P  < 0.001). Higher C7/T1 dorsal spinous processes ratios were associated with the presence of cervical ribs ( P  < 0.001), supporting this is a true homeotic transformation. Relaxation of the stabilizing selection has likely occurred, and the Pug dog appears to be a good naturally occurring model to further investigate the aetiology of cervical ribs, other congenital vertebral anomalies and numerical alterations.